2023
DOI: 10.1007/s00704-023-04788-4
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes in heatwaves and its impact on human discomfort over India due to global warming under the CORDEX-CORE framework

Pyarimohan Maharana,
Dhirendra Kumar,
Sushant Das
et al.

Abstract: Due to climate change, rapid warming and its further intensification over different parts of the globe have been recently reported. This has a direct impact on human health, agriculture, water availability, power generation, various ecosystems, and socioeconomic conditions of the exposed population. The current study thus investigates the frequency and duration of heatwaves, human discomfort, and exposure of the human population to these extremes using the high-resolution regional climate model experiments und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Singh (2023) highlights the importance of urban policies that consider the impact of heat waves on public health. An increase in the frequency and intensity of heat waves, which can lead to severe health consequences, including increased mortality and the incidence of heat-related illnesses (Maharana et al, 2024).…”
Section: Oliveira F M Et Al (2024) Content Analysis Of International ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Singh (2023) highlights the importance of urban policies that consider the impact of heat waves on public health. An increase in the frequency and intensity of heat waves, which can lead to severe health consequences, including increased mortality and the incidence of heat-related illnesses (Maharana et al, 2024).…”
Section: Oliveira F M Et Al (2024) Content Analysis Of International ...mentioning
confidence: 99%
“…The excerpt reinforces the authors' analysis by linking the intensification of heat waves to the human-caused climate crisis. Maharana et al (2024) project an increase in the frequency and intensity of heat waves in India, which could lead to severe health consequences, including increased mortality and incidence of heat-related illnesses. "A study found that heat waves have killed more than 24000 people in the country since 1992."…”
Section: Categories Of Analysismentioning
confidence: 99%